The effect of the maturity gap on delinquency and drug use over the life course: A genetically sensitive longitudinal design. (December 2016) - Nedelec, Joseph L.; Park, Insun; Silver, Ian A.
Abstract: Purpose: Relatively few studies have assessed Moffitt's claims regarding the etiology of the offending groups in her taxonomic theory. This gap is especially evident regarding adolescence-limited (AL) offending where empirical analyses of the maturity gap (the disjunction between biological and social maturity during adolescence) have produced mixed findings. Additionally, genetically sensitive analyses of the effect of the maturity gap on delinquency is entirely lacking from the literature. The current study provides such an analysis. Methods: Using a sample of monozygotic (MZ) twins ( N Indviduals = 524; N Twin pairs = 262) the current study addresses these gaps in the literature by assessing the influence of the maturity gap, parental conflict, and other theoretically relevant variables on delinquency and substance use in a sex-differentiated longitudinal analysis of MZ difference scores. Results: Findings illustrated minimal influence of the maturity gap, parental conflict, and low self-control on delinquency and substance use in adolescence and adulthood. However, discordance in exposure to delinquent peers was associated with delinquency and substance use in adolescence but with little long-term effect. Conclusion: Overall, the findings provide mixed support for Moffitt's ideas and illustrate the confounding effects of genetic factors in assessments of the etiology of antisocial behavior and tests of criminological theory. Highlights: MZ twin discordance was used to test the effect of a maturity gap on delinquency. Results illustrated little effect of a maturity gap and other control variables. Results did show an influence of delinquent peers but with no long-term effect. Analyses illustrate the importance of genetically sensitive designs in testing theory.